The impact of improved agricultural technologies on household food security of smallholders in Central Ethiopia: An endogenous switching estimation. Issue 2 (23rd July 2021) - Hailu, Mekonnen; Tolossa, Degefa; Girma, Anteneh; Kassa, Belay
Abstract: Combinations of improved agricultural technologies adoption have a significant effect on agricultural productivity and household food security. Their synergies improve soil fertility and suppress weeds, pests, and diseases. Many studies in Ethiopia analyze the impacts of improved technologies adoption in isolation rather than in combinations; little attention was given on multiple combinations of improved technologies adoption on household food security. This study analyses the impact of combinations of improved agricultural technologies adoption on household food security (per capita calorie consumption, dietary diversity score, and food consumption score). Data were collected from household survey questionnaire, focus group discussions, and key informant interviews. An endogenous switching regression model is applied to analyze the impacts through adoption decisions by farm households which can be adopted in various combinations. We find that the adoption of improved agricultural technologies increases dietary energy supply, dietary diversity, and food consumption score significantly and the greatest impact is obtained when improved technologies adopting in combinations rather than in isolation. The adoption of multiple combinations of improved technologies has substantial effects that improve the food security status of smallholders in the study areas. This implies that agricultural research, extension, policymakers, and other actors to promote a combination of improved agricultural technologies to improve household food security through increasing productivity and income.